Communication Skills - A. V. Raychenko (Управление)
A key role in the formation, functioning and development of modern social organization plays communication, as a basis to establish, maintain and develop constructive relationships, connections and interactions that ensure consistent and effective achievement of personal, group and social goals. The ability to install, functionally diversify and expand communication in and outside the organization, largely determined by the skill level of the leader, determined, first of all, by business and personal qualities of constructive interactive leader. Development of professional achievements of effective communication the founder and the first head of the department of scientific bases of management of the Moscow engineering-economic institute has formed at its creation, in the making and provides, for the past fifty years, deserved recognition, full support and the progressive development of ideas, effective creative collaboration of students, supporters and followers of the doctor of economic sciences, professor Olimpiada Vasilievna Kozlova.